Zagłada miasta. Warszawa w Pianiście Romana Polańskiego - Jazdon, Mikołaj (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
The Annihilation of a City. Warsaw in Roman Polanski’s The Pianist This article is an analysis of Roman Polanski’ The Pianist, focused on presenting how the city space in this film, both its exteriors and interiors, makes it a story of Warsaw during the Second World War. The gradual destruction of the city is presented in two supplementary fashions. On the one hand, there is as a quasi-documentary reconstruction of the past based on literary (Władysław Szpilman’s diary) and visual (archive photographs and films) material, while on the other, there is a symbolic narration, where particular places and events bear hidden meanings. Next to Chopin and his music, the piano, interiors and city walls, the most meaningful symbol in the film is a monument of Jesus Christ carrying the cross, a statue standing in front of The Church of the Holy Cross in Warsaw, a motif that appears in the second shot of the Pianist and returns three more times during the film.